2005
DOI: 10.2131/jts.30.91
|View full text |Cite
|
Sign up to set email alerts
|

A Time-Course Characterization of Male Reproductive Toxicity in Rats Treated With Methyl Methanesulphonate (Mms)

Abstract: -Methyl methanesulphonate (MMS), a potent alkylating agent and testicular toxicant, was orally administered to rats for 5 days at doses of 20, 30, and 40 mg/kg. During the recovery period of 5 weeks, males were evaluated for multiple endpoints such as organ weights, fertility, and sperm parameters. The 5-week recovery periods are designated as follows: Day 1 (1 day after final treatment); Week 1, Week 2, Week 3, Week 4, and Week 5 (first, second, third, fourth, and fifth week after final treatment). A clear ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 23 publications
(32 reference statements)
0
8
0
Order By: Relevance
“…So, we suggest that the rat is also a very important model for the investigation of the mechanisms and susceptibility of germ cells to genotoxicity. After MMS treatment, the sensitive cellular stage for induction of sperm morphological abnormalities was judged to be late spermatids [Kuriyama et al, ]. These results also indicated that all three compounds induced DNA damage in isolated germ cells in mouse as well as shown earlier in rat so strengthening the rodent data base.…”
Section: Discussionmentioning
confidence: 89%
“…So, we suggest that the rat is also a very important model for the investigation of the mechanisms and susceptibility of germ cells to genotoxicity. After MMS treatment, the sensitive cellular stage for induction of sperm morphological abnormalities was judged to be late spermatids [Kuriyama et al, ]. These results also indicated that all three compounds induced DNA damage in isolated germ cells in mouse as well as shown earlier in rat so strengthening the rodent data base.…”
Section: Discussionmentioning
confidence: 89%
“…For the micronuclei test a positive control group (Pc n ¼ 5) received water and one dose of methyl methanesulfonate (MMS -Sigma, St. Louis, MA, USA) at a concentration of 20 mg/kg 24 h before euthanasia [17].…”
Section: Fluoride Administrationmentioning
confidence: 99%
“…Thereafter, 3 mL biuret reagent received 50 mL of the sample. After 10 min, the samples were read at 540 nm, and the mean was used to calculate protein concentration in the sample with the following equation: absorbance e 0.0026/0.0073 17 . The pellet containing the mitochondrial fraction (0.5 mg protein), added to 3 mL medium containing 125 sucrose and 1 mM HEPES, pH 7.2e7.3, furnished absorbance kinetically monitored at 540 nm over a period of 15 min.…”
Section: Evaluation Of Damage To Liver Mitochondriamentioning
confidence: 99%
“…The animals were weighed, and received by gavage, an aqueous solution of ametryn (T1 and T2) or water only (Co) for a chronic period of 56 days. For the micronucleus test, a positive control group (PG) (n = 6) received by gavage water and, one day before the euthanasia, a single dose (20 mg/kg) of methyl methane sulfonate (MMS) (Kuriyama et al, 2005).…”
Section: Experimental Delineationmentioning
confidence: 99%